Program Manajemen Stres Kerja di Perusahaan: sebuah Petunjuk untuk Menerapkannya - Susy Purnawati (Buletin Psikologi, 2014)
Job stress is an iceberg phenomen. A great number of unreported cases and there is no aplicativeprogram in Indonesia cause increase of job stress risk and its negative impact to productivity andcompany image. More complex job demand without appropriate work capacity and inharmonicrelationship in the work place could be the main sources of job stress. This paper is focused on jobstress management program guidance that applicable at company and physiologic stress responseand also in depth theoretical point of job stress management within psycho-physiology aspect. Theaim of this written paper is to increase awareness and understanding of the application of stressmanagement programs among occupational physician, industrial community and industrialpractices. Stress management programs in company not only post about the improvement ofworking conditions also focuses on an individual orientation. On aspects of working conditions, theimprovement should be referring to standard of occupational health and safety (OHS) -management program, while aspect of individual coping skills can be done with the training ofproblem focus technique. Several studies have shown that the program creates respond to the limbicsystem of brain which is integrated with the function of cortex frontals. In addition, it could createrespond to changes body’s homeostasis due to changes in the response of the limbic system to theHPA (hypothalamic - pituitary - adrenal) axis and SAM (symphato - Adreno - medullary) - axis.The effectiveness of the program can be measured by the subjective and objective parameters.